Extraction and Purification of Pseudomonas aeruginosa Lipopolysaccharide Isolated from Wound Infection (World Journal of Experimental Biosciences, 2017)
Samples were obtained from patients suffering from burns and wounds and then identified using the biochemical tests and the VITEK 2 fluorescent system. The tests confirmed the presence of Pseudomonas aeruginosa. Antibiotic susceptibility testing showed that the isolate was sensitive to piperacillin, ceftazidime, cefepime, imipenem, meropenem, amikacin, gentamicin, tobramycin, ciprofloxacin and levofloxacin while resistant to ampicillin, cefazolin, ceftriaxone, tigecycline and trimethoprim/sulfamethoxazole. The lipopolysaccharide (LPS) was extracted by the hotEDTA method and partially purified by gel filtration chromatography using the Sephadex G-200.